High-performance Monte Carlo Simulation of Multilayer Magnetic Films - V.Yu.В Kapitan; A.V.В Perzhu; K.V.В Nefedev (Журнал нано- та електронної фізики)
The results of numerical calculations of the thermodynamic properties of multilayer films with alternating magnetic and non-magnetic layers were presented. Computer simulation of such structures within the frame of the classical Heisenberg model was carried out by Monte Carlo methods. The processes of magnetization reversal of multilayer structures in external magnetic fields were investigated.